Anxiety and Concentration of Tennis Athlete - Rices Jatra; Septian Raibowo (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2021)
The purpose of this research to understand the correlation between anxiety and the concentration of tennis athletes. The subjects of this study were tennis athletes who entered the qualifying round in the " Piala Rektor UNP & Dirut Bank Nagari 2021" tournament as many as 50 people. Measurement of anxiety variables on the sports anxiety scale and concentration variables using a concentration training grid. Analysis of the data used is product moment correlation. Analysis of the data used is product moment correlation. Data analysis shows a correlation coefficient of 0.784 and is included in the strong category and contributes to the correlation between variables of 0.64 or 64%. From the value of the correlation coefficient is in the strong category. That is, if the level of anxiety is high, the level of concentration of tennis athletes will be lower and vice versa, an increase in concentration will be followed by a decrease in anxiety.